Mono- and binuclear non-heme iron chemistry from a theoretical perspective - Rokob, Tibor András; Chalupský, Jakub; Bím, Daniel; Andrikopoulos, Prokopis C; Srnec, Martin; Rulíšek, Lubomír (Journal of biological inorganic chemistry, 2016)
In this minireview, we provide an account of the current state-of-the-art developments in the area of mono- and binuclear non-heme enzymes (NHFe and NHFe2) and the smaller NHFe(2) synthetic models, mostly from a theoretical and computational perspective. The sheer complexity, and at the same time the beauty, of the NHFe(2) world represents a challenge for experimental as well as theoretical methods. We emphasize that the concerted progress on both theoretical and experimental side is a conditio sine qua non for future understanding, exploration and utilization of the NHFe(2) systems. After briefly discussing the current challenges and advances in the computational methodology, we review the recent spectroscopic and computational studies of NHFe(2) enzymatic and inorganic systems and highlight the correlations between various experimental data (spectroscopic, kinetic, thermodynamic, electrochemical) and computations. Throughout, we attempt to keep in mind the most fascinating and attractive phenomenon in the NHFe(2) chemistry, which is the fact that despite the strong oxidative power of many reactive intermediates, the NHFe(2) enzymes perform catalysis with high selectivity. We conclude with our personal viewpoint and hope that further developments in quantum chemistry and especially in the field of multireference wave function methods are needed to have a solid theoretical basis for the NHFe(2) studies, mostly by providing benchmarking and calibration of the computationally efficient and easy-to-use DFT methods.
Keywords: Reactivity; Non-heme iron; Multireference methods; Nonheme Iron Proteins; Humans; nehemové proteiny obsahující železo; Quantum Theory; Density functional theory; Dioxygen activation; lidé; kvantová teorie